Study of Magnetic Susceptibility of Ge4+ Doped Cu-Zn Ferrite - Padampalle, Ashok S. (Journal for Research in Applied Sciences and Biotechnology, 2022)
Polycrystalline spinel ferrite Cu_(0.7+x) Zn_0.3 Ge_x Fe_(2-2x) O_4 where x= 0.0, 0.1 to 0.6 prepared by standard double sintered ceramic method. The a. c. susceptibility measurements on powdered samples were made using double coil set up. A specimen is kept in the center of a balanced double coil which itself is at the center of a Helmholtz coil system producing an alternating magnetic field behaves like an alternating dipole and induces a differential emf in the double coil. cT/cRT does not vary with temperature. As composition of Ge4+ is increased the Curie temperature (Tc) decreases. Near the Curie temperature there is sharp decrease of cT/cRT suggesting the single-phase formation of material.